Okra (Abelmoschus Esculentus) As Food Substitute to Increase Fiber and Protein Content of Fungal Fermented Food - Dian Yustika Rini; Arif Sabta Aji; Veriani Aprilia; Herni Dwi Herawati; Rosi Novita; Syuja Rafiqi Arifin (Ikatan Sarjana Gizi Indonesia (ISAGI), 2021)
Fungal fermented foods, such as tempe, are nutritious, affordable, and a good source of protein. Nuggets are known as chicken-based ultra-processed food. However, Tempe as raw materials is rarely processed. The combination of Tempe nuggets and additional Okra could improve the nutritional content such as protein and fiber. The current study aimed to investigate the correlation between additional Okra in Tempe nuggets product and nutritional content, and sensory characteristics of fungal fermented food. Experimental design research was conducted from May to July 2019. A total of three treatments and three repetitions were carried out to develop this product including A1 (85% Okra and 15% Tempe flour), A2 (75% Okra and 25% Tempe flour), and A3 (65% Okra and 35% Tempe flour). Semi-trained panelists were selected to perform the sensory test. Protein and fiber of produce were assessed by Kjeldahl method and the soxhlet method. The results indicated that Okra substitution was significantly liking of the color, taste, and aroma of the product (p<0.05), but not in texture indicator (p=0.06). The protein content of the product increased significantly in the A3 formulation. However, the fiber content had no significant difference between Tempe and Okra substitution (p=0.38). Okra has potential dietary food substitution to increase the protein of the fungal fermented food product. The combination formula of Tempe and Okra has a significant impact on the level of preference in color, flavor, and aroma of the Tempe nugget product. Future researches are required to confirm this finding and contribute to the development of Tempe nugget product.